Recurrence–Preventive Role of Flatus Tubes Following Endoscopic Decompression in Sigmoid Volvulus - Atamanalp, Sabri Selçuk; Dişçi, Esra; Peksöz, Rıfat; Korkut, Ercan; Aksungur, Nurhak; Altundaş, Necip; Kara, Salih (Turkish Journal of Gastroenterology, 2023)
Background: Sigmoid volvulus may recur following endoscopic decompression. Flatus tubes are traditionally used to prevent an early recurrence. This study aims to evaluate the recurrence–preventive role of the flatus tubes in sigmoid volvulus.Methods: Sigmoid volvulus recurrence was retrospectively analyzed in prospectively collected clinical data of endoscopically decompressed 60 patients, in whom no tube, rectal tube, or sigmoidal tube was used.Results: Mean pain/discomfort scores were higher in rectal and sigmoidal tube groups than that of no tube group (1.2 ± 0.4, 4.2 ± 0.9, and 3.5 ± 0.9, respectively, P < .001). The early recurrence was seen in 3 patients in the no tube group, while no early recurrence was determined during tube placement in the rectal and sigmoidal tube groups (15.0%, 0.0%, and 0.0%, respectively, P < .05, P < .05, and P > .05). The tubes were removed or spontaneously discharged in 13 (65.0%) and 12 patients (60.0%) in the rectal and sigmoidal tube groups, respectively, and sigmoid volvulus recurred in 2 patients in each group following the removal or spontaneous discharge. There was no statistically significant difference between the early recurrence rates of the no tube, rectal tube, and sigmoidal tube groups following the removal or spontaneous discharge of the tubes (15.0%, 15.4%, 16.7%, respectively, P > .05) and in total (15.0%, 10.0%, and 10.0%, respectively, P > .05).Conclusion: Flatus tubes may prevent the early volvulus recurrence during their placement in sigmoid volvulus. Nevertheless, they generally cause pain and discomfort, and they are frequently removed or spontaneously discharged, which suppresses their recurrence– preventive effects.Cite this article as: Atamanalp SS, Dişçi E, Peksöz R, et al. Recurrence–preventive role of flatus tubes following endoscopic decompression in sigmoid volvulus. Turk J Gastroenterol. 2023;34(4):371-377.